2008
DOI: 10.1371/journal.pgen.1000038
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping of the Psoriasis Susceptibility Locus PSORS1 Supports HLA-C as the Susceptibility Gene in the Han Chinese Population

Abstract: PSORS1 (psoriasis susceptibility gene 1) is a major susceptibility locus for psoriasis. Several fine-mapping studies have highlighted a 300-kb candidate region of PSORS1 where multiple biologically plausible candidate genes were suggested. The most recent study has indicated HLA-Cw6 as the primary PSORS1 risk allele within the candidate region in a Caucasian population. In this study, a family-based association analysis of the PSORS1 locus was performed by analyzing 10 polymorphic microsatellite markers from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 48 publications
2
58
0
Order By: Relevance
“…10,11 Although all three SNP signals in the MHC are allied with coding variants of nearby genes, our finding remains that the SNPs are more strongly associated with disease than the putative causative gene variants. For the best SNP signal, this stronger association was demonstrated to be an artifact of reduced imputation quality.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…10,11 Although all three SNP signals in the MHC are allied with coding variants of nearby genes, our finding remains that the SNPs are more strongly associated with disease than the putative causative gene variants. For the best SNP signal, this stronger association was demonstrated to be an artifact of reduced imputation quality.…”
Section: Discussionmentioning
confidence: 85%
“…As assessed using phase I 1000 genomes data set, our primary signal in the MHC (rs114255771) exhibited complete LD (r 2 ¼ 1) with rs4406273 chr6.hg19.g.31266090G4A. This SNP was the primary hit in that meta-analysis and also happens to be an excellent surrogate for HLACw*0602, the leading candidate for the PSORS1 risk allele 10,11 (unpublished data). Our secondary MHC signal (rs6924962) is in close proximity (B8.9 kb) to and exhibits moderately strong LD (r 2 ¼ 0.56) with the secondary MHC signal from the GWASImmunochip meta-analysis (rs13437088 chr6.hg19.g.3135511T4C).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This observation widens the spectrum of molecular defects causing PSS type B and shows that loss of five additional genes in the PSORS1 region does not result in an additional cutaneous phenotype. Fine-mapping studies have previously shown that the strongest predisposing gene to psoriasis within the PSORS1 region is HLA-CW6, while TCF19, CCHCR1 (HCR), PSORS1C1 (previous SEEK1), PSORS1C2 (SPR1), C6orf15 (STG) show a weaker association (6,7). Several of these genes have been associated with type 1 diabetes (TCF19, CCHCR1 and PSORS1C1) (8), systemic sclerosis (PSORS1C1) (9) or follicular lymphoma (C6orf15 or STG) (10) features which are not seen in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Oxazolone (OX) and 2,4-dinitrofluorobenzene (DNFB) are haptens inducing exacerbation of allergy accompanied with allergen-specific T cells (7,8). OX was applied to mouse ear with various schedules, and inflammatory cytokines mRNA expression was measured by quantitative PCR.…”
Section: Questions Addressedmentioning
confidence: 99%